Subjectivity in the Age of Pandemics - Mensch James (De Gruyter, 2021)
The current pandemic that originated in a “wet” market in Wuhan has often been compared to the threat we face with climate change. The former originated in the trade in wild animals, which has driven many species to the point of extinction. In fact, we face an unprecedented rate of species loss due to pressures on habitats, pollution, and human predation. The threat of climate change originates with our uncontrolled use of fossil fuels, which, in making large parts of the globe uninhabitable, imperils our own species. The rationality (or lack thereof) that is exhibited here concerns our relation to the earth. We regard it simply as a means for our purposes. Separating ourselves from it, we follow the Biblical injunction to have “dominion” over it. In this, we express a conception of subjectivity that is exemplified by Descartes and Kant. To overcome this, I argue, we need a different sense of what it means to be a subject, one that takes it as a sustaining ground and points to the earth as the ultimate subject.